MEASUREMENTS OF INEQUALITY IN POLITICAL METAMODERNISM (HANZI FREINACHT) AND THE AGE OF ACCESS (JEREMY RIFKIN) - Maniukov , Oleksandr (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2021)
The article covers a multidimensional issue of social inequality. Most of sociological and philosophical studies concern informational, economic and gender inequality. However, for holistic understanding of the problem, it is important to take into account emotional, ecological and psychological components. Informational, economic and ecological inequality directly depend on access to truthful and scientifically based information from reliable sources, to opportunities of supporting oneself financially, to quality food products and safe environment, respectively. To overcome these types of inequality, access should be taken into account, as a concept, characteristics of which define the availability and accessibility of certain resources and the ability to satisfy either the need in clean drinking water or one’s social recognition by others. The correlations between the concept of “Age of Access” coined by Jeremy Rifkin and Hanzi Freinacht’s theory of metamodern politics are presented. The relevance of “access” to multidimensional inequality (one of the issues ideologists of political metamodernism work on) was analysed. A cohort of central actors in the age of access was reviewed. It includes metamodern aristocracy (hackers, hippies, hipsters, hermeneutics) and a group formed by cleanweb‑, bio‑, info‑ and 3D‑hackers. It was demonstrated that the abovementioned specialists are deeply involved in the regulatory processes of access control and/or its deprivation compared to other members of post-industrial societies. In post-industrial societies with networked economy the role of access has significantly increased relatively to accumulation of material wealth and property ownership. On the one hand, building a just society requires overcoming the forces that somehow perpetuate inequality, and, on the other hand, providing the highest possible level of access to everything that increases equality between people. Those who are excluded from networks and deprived of access should not be forgotten; they don’t have access not only to resources, but can’t even have a discussion with the privileged ones about their own inferior condition. The reproduction mechanisms of the above-mentioned types of inequalities should be complemented by such a concept of access that would contribute to the eradication of inequality and/or provide us with more equitable solutions in case of insurmountable circumstances. Such solutions also might be applied to emotional and psychological inequality.